Behavioural activation interventions for depression and well-being - Mazzucchelli, Trevor G. (Curtin University, 2010)
Behavioural activation (BA) treatments for depression require patients to change their overt behaviour so that they may have more rewarding experiences in their lives. Since one of the most promising ways to increase psychological wellbeing is to increase engagement in valued and enjoyable activities, there is good reason to believe that BA may also be an effective intervention to increase wellbeing. Enhancing well-being is an important goal because there is increasing recognition of the positive impact well-being has on many desirable life outcomes such as career success, marriage and health. Although BA has existed since the 1970s there have been surprisingly few quantitative reviews of the literature, and little research on the impact of BA on well-being. Thus, the overall aim of this project was to consolidate our understanding of the impact of BA and investigate the potential of BA interventions for enhancing well-being. Specifically, the goals were to (a) review the existing empirical research on the utility of BA for treating depression, (b) review the existing research on BA related to well-being, and (c) investigate the potential of this approach to increase the well-being of individuals who are not suffering from a mental health problem. Thus this research is unique in not only focusing on clinical, depressed, individuals, but also integrating research from the field of positive psychology as it looks at improving the well-being of individuals without depression.The first study consisted of a meta-analysis which sought to identify all randomised controlled trials of BA for depression. The goal of this study was to determine the effect of this approach, and examine the differential effectiveness of variants. Forty studies with 2,401 participants reporting symptoms of depression were included. The pooled effect size (Hedges’s g) indicated the difference between BA and control conditions at posttest was 0.91. For participants who satisfied the criteria for major depressive disorder (MDD) the overall effect size of 0.82 remained large and significant. No differences in effectiveness between BA and cognitive therapy were found. This is an important finding given that BA is a comparatively simple intervention that does not require difficult or complex skills from patients or therapists. Although more recent versions of the BA approach, such as Jacobson and colleagues’ contextual BA, generally yielded greater intervention effects compared with earlier variants, all variants produced effects of similar magnitude and differences between them were not statistically significant. Nevertheless, a focused evidence review indicated that Jacobson and colleagues’ contextual BA has the strongest evidence base and satisfies the APA’s Division 12 Task Force’s well-established designation for the treatment of MDD.Study 2, also a meta-analysis, sought to identify all randomised controlled studies which examined the effect of BA on well-being. Twenty studies with a total of 1,353 participants were included. The pooled effect size indicated that the difference in well-being between BA and control conditions at posttest was 0.52. This significant effect, which is comparable to the pooled effect achieved by positive psychology interventions, was found for nonclinical participants and participants with elevated symptoms of depression. This suggests that BA is a useful intervention for promoting the well-being of a range of populations in both clinical and nonclinical settings.Study 3 examined the effects on well-being of a group intervention consisting of a 4-week BA component followed by a 3-week mindfulness component, finishing with an integrating closure session. Sixteen nonclinical adults recruited from the community participated in this pretest-posttest, repeated measures study. Results showed moderate and significant improvements in psychological distress and several indices of well-being after the BA component. These improvements continued through the mindfulness component of the intervention such that effects were greater after participants had received the complete intervention. Half of the participants reported reliable and clinically significant improvement in the amount of time they felt happy after the intervention and a quarter of participants reported improvement at follow-up.Taken together, these results led to the conclusion that BA is a well-established and advantageous intervention for depression which is also an effective and viable intervention for well-being, regardless of individuals’ depression status. The use of BA as a first line treatment for depression is recommended. However, further research is needed to determine whether BA interventions can be made more efficient, and to determine the full extent of their potential to promote mental health.